The Internet in New Zealand 2013 - Gibson, A; Miller, M; Smith, P; Bell, A; Crothers, C (Institute of Culture, Discourse & Communication, AUT University, 2013)
Executive Summary The fourth survey of the World Internet Project New Zealand (WIPNZ) was conducted between late July and early September 2013. For the first time, the sample in 2013 used both telephone and internet surveys. This report presents an analysis of the usage of and attitudes to the internet of the resulting sample of 2006 New Zealanders. As internet use approaches saturation in New Zealand, our focus turns from ‘how many people use the internet?’ to ‘how do people use the internet?’ and ‘why do some not use the internet at all?’ To answer these questions, the sample has been divided into five categories: never-users (5% of sample), ex-users (3%), low level users (14%), first generation users (40%) and next generation users (38%). Usage For a large number of people the internet is used daily. Four out of five spend an hour or more online at home every day. Almost everyone under 40 is online, so that only 1% of our under-40 sample are non-users. Accessing the internet ‘on the go’ is prevalent. Seven out of ten users access the internet from a hand-held mobile device such as a smartphone or an iPad. Almost half of the internet users surveyed (48%) said that they had accessed the internet through a tablet, while an even higher proportion (68%) connected through their mobile phone in the past year. Activities Most internet users say they surf or browse the web (96%) or visit social networking sites (81%). 34% of internet users report that they use the cloud, 41% purchase apps and almost two thirds (65%) download free apps. Most users check their email daily (89%). Just over 60% of men aged 30–44 said they have looked at sites with sexual content. Māori and Pasifika internet users, especially those in lower income households, take the lead in subscriptions to music streaming services like Spotify. More than one in five Māori (21%) and Pasifika (23%) users in households with annual incomes of less than $50,000 have paid for a subscription to a music streaming service in the past year. The internet is used as a tool for consumer decision making, with 94% of users looking for information about products online – more than half of users do this at least weekly. For 85% of users, this kind of online research includes comparing prices. Almost half of our users (47%) have logged in to secure areas on Government or Council websites, and 51% have paid taxes, fines or licences online in the past year. Comparing the importance of media Comparing the importance of various forms of media as information sources, 81% of all our respondents rated the internet (including online media such as streamed radio) as important or very important. This was very much higher than the proportion who rated offline media as important: television (47%), radio (37%) and newspapers (37%). One of the most dramatic differences according to age group is the importance of the internet as a source of entertainment and leisure. While watching (offline) television is an important leisure activity for people across all ages, using the internet as a form of entertainment is a young-person phenomenon: 80% of respondents aged 16–29 rate it as important or very important. This 2013 survey has a different sample structure than previous years in order to include New Zealanders without a landline. The questionnaire has also undergone substantial updating to keep pace with changing digital technologies. For these reasons, the present report focuses solely on the findings for 2013, and longitudinal analyses will be presented in a subsequent report next year.